Price Discontinuities in an Online Market for Used Cars - Englmaier, Florian; Schmöller, Arno; Stowasser, Till (Management Science, 2018)
We study the price-setting behavior in a competitive market for used cars and provide empirical evidence for coarse information processing. Based on detailed field data from one of Europe’s largest online marketplaces for automotive vehicles, we document systematic and sizable price discontinuities at salient car-age and mileage thresholds. The price difference between two otherwise identical cars across registration years (where one was first registered in January and the other in December of the previous year) is up to five times larger than that between two cars first registered in any two subsequent months within a registration year. A similar pattern can be observed in the mileage dimension at 10,000-km odometer marks, which is in line with earlier findings in the literature. Being able to study discontinuities along two dimensions of the same good allows us to further our understanding toward a more general notion of inattentive behavior. While our results are compatible with a behavioral model of limited attention, we also provide evidence for a more traditional explanation based on search frictions. Data and the online appendix are available at https://doi.org/10.1287/mnsc.2016.2714 . This paper was accepted by Uri Gneezy, behavioral economics.